Developing Religious Culture through Integrative Religious Practice in Indonesian State Islamic University - Ali, Nur; Miftahusyai'an, Mohammad; Prasetyo, Angga Teguh; Muttaqin, Muhammad Imamul (el Harakah: Jurnal Budaya Islam, 2020)
Higher education has been accused as an environment which has less moral and religious values. The negative stereotype became more evident when some higher education institutions involved in some disputes such as brawl among students, and riots in Ramadhan and at the time of sahur. There is also State Islamic Higher Education Institution (PTKIN) among the campuses. However, some SIHEIs have constructed religious culture through Integrative Religious Practices (IRP). The paper aims at evaluating the IRP as a strategy in building campus religious culture. Interview, participant observation, and data analysis lead to the finding that IRP development was formally done in class and was informally and ceremonially applied outside the class through ma’had, students’ organizations, cooperation with religious institutions, and relation across region and professions can build campus religious culture. Moreover, it also improves students’ ethical behavior, empathy, and tolerant. The study suggests that religious subject in higher education and schools is developed using IRP and involves relevant units and religious organizations outside campus to improve the understanding on the socio-religious value to establish ethical, tolerant, empathy, and cooperative behavior. Perguruan Tinggi telah dituduh sebagai lingkungan yang kurang mencerminkan nilai-nilai moral dan religius. Stereotip buruk ini makin diperkuat dengan keterlibatan PT dalam beberapa kericuhan seperti tawuran mahasiswa serta tawuran di bulan Ramadhan dan di waktu sahur. Di antara perguruan tinggi tersebut terdapat Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Namun ada juga PTKIN yang telah membangun budaya religius melalui Praktik Keagamaan Integratif (PKI). Tulisan ini mengevaluasi PKI sebagai strategi dalam membangun budaya religius di kampus. Wawancara, observasi partisipan, dan analisis data yang dilakukan menghasilkan temuan bahwa pengembangan PKI yang dilakukan secara formal di kelas dan diaplikasikan nonformal dan seremonial di luar kelas melalui ma’had, organisasi kemahasiswaan, kerjasama dengan lembaga keagamaan, dan pergaulan lintas daerah dan profesi dapat membangun budaya religius di kampus. Selain itu, hal itu juga dapat menumbuhkan sikap etis, empati, dan toleran di kalangan mahasiswa. Tulisan ini menyarankan agar materi keagamaan di PT dan sekolah dikembangkan dengan praktik keagamaan integratif dan melibatkan berbagai unit terkait dan organisasi keagamaan di luar kampus untuk meningkatkan pemahaman nilai-nilai sosial-keagamaan sehingga menumbuhkan perilaku agamis, toleran, empati, dan sikap saling menghargai.